Social change in a material world : how activity and material processes dynamize practices - Schatzki, Theodore R. (London : Routledge, 2019)
Social Change in a Material World offers a new, practice theoretical account of social change and its explanation. Extending the author's earlier account of social life, and drawing on general ideas about events, processes, and change, the book conceptualizes social changes as configurations of significant differences in bundles of practices and material arrangements. Illustrated with examples from the history of bourbon distillation and the formation and evolution of digitally-mediated associations in contemporary life, the book argues that chains of activity combine with material events and processes to cause social changes. The book thereby stresses the significance of the material dimension of society for the constitution, determination, and explanation of social phenomena, as well as the types of space needed to understand them. The book also challenges the explanatory significance of such key phenomena as power, dependence, relations, mechanisms, and individual behavior. As such, it will appeal to sociologists, geographers, organization studies scholars, and others interested in social life and social change.
On changes, events, and processes -- The practice plenum -- 3.the material dimension of social life -- Social dynamics I: chains of activity -- Social dynamics II: material events and processes -- Explaining social changes -- Dealing with complexity: overviews -- Challenging social theoretical stalwarts -- List of references -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Social change; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General